2020
DOI: 10.1002/jcp.29511
|View full text |Cite
|
Sign up to set email alerts
|

A 16‐mRNA signature optimizes recurrence‐free survival prediction of Stages II and III gastric cancer

Abstract: High‐throughput messenger RNA (mRNA) analysis has become a powerful tool for exploring tumor recurrence or metastasis mechanisms. Here, we constructed a signature to predict the recurrence risk of Stages II and III gastric cancer (GC) patients. A least absolute shrinkage and selection operator method Cox regression model was utilized to construct the signature. Using this method, a 16‐mRNA signature was identified to be associated with the relapse‐free survival of Stages II and III GCs in training dataset GSE6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…[49] In our study, we presented the batch effect of GSE84437 and the normalized data after overcoming this disadvantage, making our prognostic signature more robust and reliable. Although the 1-,3-,5-year AUC of our 6-URGs prognostic signature are lower than that of former studies [42][43][44][45][46][47][48] (most AUC > 0.7), this doesn't imply a lower prediction performance of it as a big sample size (406 and 431 in our case) can strongly affect the AUC of a model and AUC can even close to 0.5 when sample size is larger than 500. [50] It is necessary to search the underlying mechanisms of the 6 UPR genes identi ed in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…[49] In our study, we presented the batch effect of GSE84437 and the normalized data after overcoming this disadvantage, making our prognostic signature more robust and reliable. Although the 1-,3-,5-year AUC of our 6-URGs prognostic signature are lower than that of former studies [42][43][44][45][46][47][48] (most AUC > 0.7), this doesn't imply a lower prediction performance of it as a big sample size (406 and 431 in our case) can strongly affect the AUC of a model and AUC can even close to 0.5 when sample size is larger than 500. [50] It is necessary to search the underlying mechanisms of the 6 UPR genes identi ed in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…There are several studies having established multi-molecule biomarkers for GC prognosis including mRNAs, non-coding RNAs, DNA methylation, and so on. [42][43][44][45][46][47][48] All these models demonstrated good prediction effect for OS or RFS (Recurrence free survival) of GC. But seldom of them provided a detailed description of normalization process with GEO array express data.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that these molecules can not only act as oncogenes or tumor suppressor genes but also participate in the occurrence and development of tumors through a complex mutual regulatory network ( Mirgayazova et al, 2019 ). Besides, their expressions are tumor-tissue specific and have the potential as diagnostic or prognostic markers ( Sim et al, 2018 ; Hou et al, 2020 ; Peng et al, 2020 ). Therefore, it is urgently needed to investigate the integration of multiple RNA expression profiles to identify molecular signatures.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the American Joint Committee on Cancer (AJCC) stage is still the most basic prognostic prediction tool for gastric cancer, and a high stage indicates a poor prognosis. However, due to the high heterogeneity of gastric cancer, patients with the same tumor-node-metastasis (TNM) stage may have different prognoses ( 16 ). Similarly, differences in responses to immunotherapy among patients may also be related to their genetic and molecular backgrounds.…”
Section: Introductionmentioning
confidence: 99%